PENGARUH PELAKSANAAN INISIASI MENYUSU DINI (IMD) TERHADAP LAMA PERSALINAN KALA III PADA IBU BERSALIN DI RUMAH SAKIT UMUM DAERAH DAN RUMAH BERSALIN GRATIS KOTA YOGYAKARTA TAHUN 2010 - Susilo Rini; RA Aminah Maya (Universitas Harapan Bangsa Purwokerto, 2010)
Backround: Indonesia had high number of maternal mortality and one of the causes was caused of bleeding in delivery. The number of bleeding at RSUD Yogyakarta increases from0,93% in 2008 to 1,88% in 2009, meanwhile at RBG Yogyakarta in 2009 the number ofbleeding was 0%. One of the ways to prevent the bleeding is by doing early breastfeedinginitiation that can stimulate utery contraction so that can make duration of third stage of laborfaster and decrease the bleeding in delivery. Althuogh the beneficients of IMD have beenknown, but there are still many hospitals and others health service places haven’t done IMD. Objectives :the purpose of this research was to know the effect of early breastfeedinginitiation to the duration of third stage of labor by delivery mother in RSUD and RBGYogyakarta City at 2010 Methods : this study was experiment research by using static group comparison of praexperiment design. The locations are in RSUD and RBG Yogyakarta city. In this researchused early breastfeeding initiation as independent variable and duration of third stage of laboras dependent variable.the data scale used nominal and rasio. The samples were 60 personsfrom population that fulfill the criteria. Data analysis used independent t-test to understandthe effect of early breastfeeding initiation to the duration of third stage of labor. Result : from 60 respondents, 30 persons (50%) being experiment group and 30 persons(50%) being control group and the average duration of third delivery phase for experimentgroup were 6,10+1,67 minutes and for control group 9,73+1,89 minutes. t-account (7.888)was higher than t-table (1.671) ) and p value = 0,000 (p < 0,05) so Ho was unacceptable andit means that there was an effect of early breastfeeding initiation to the duration of third stageof labor Conclutions: there was an effect of early breastfeeding initiation to duration of third stage oflabor by delivery mother. Keywords: early breastfeeding initiation, the duration of third stage of labor.